Case report: From misdiagnosis to timely detection: a clinical and imaging guide to neurological presentations of diffuse large B-cell lymphoma—insights from six cases - Yang, Chunxiao; Gong, Zihua; Wang, Tao; Yuan, Huijuan; Na, Weinan; Xie, Wei; Yu, Shengyuan (Frontiers in Oncology, 2025)
BackgroundThe clinical spectrum of diffuse large B-cell lymphoma (DLBCL) is notably heterogeneous. Some DLBCL patients initially present with neurological manifestations, leading to their preliminary diagnosis within neurology departments. However, the overlap of clinical and auxiliary examination findings with those of various neurological entities—such as cerebral infarction, demyelination, viral encephalitis, and peripheral neuropathy—often results in diagnostic misattribution.Case presentationWe delineate six pathologically-confirmed DLBCL cases, each heralded by neurological deficits, including limb paresis, sensory loss, vertigo, seizure activity, and aphasia. These presentations precipitated multiple erroneous diagnoses pertaining to nervous system pathologies, culminating in a median diagnostic latency of 8 months.ConclusionThe differential diagnostic process for the misdiagnosed conditions in these cases has been meticulously revisited, enhancing the diagnostic acumen of neurologists. These cases underscore the imperative for neurologists to maintain a high index of suspicion for lymphoma in atypical presentations and to judiciously integrate multimodal diagnostic modalities—such as comprehensive imaging, cerebrospinal fluid analysis, and biopsy—to expedite diagnosis and initiate timely intervention.